Policy Initiatives for Tree Planting in Private Lands - Sreedharan, C. K. (Indian Forester, 2005)
The response of the forest sector towards the liberalization and privatization set in our country has to be positive. There is need to bring in changes in laws, rules and regulations to make tree growing much more attractive and profitable in private lands. We should not miss the excellent opportunity available in the present era. Some areas where changes are required are indicated.